Legalitas Perang Irak Dan Perianggungjawabannya Dalam Hukum Internasional - Jawahir Thontowi (Jurnal Hukum IUS QUIA IUSTUM, 2005)
An agression used by USA and its allies to Irak is apparanthy not legal for the absence strong legal arguments. The inclusion ofthe use ofthe UN Resolution No. 627 and 1441, the pre-emptive strike and anticipatory self-defence are obviously contravene againts the international obligations and the general principle of international accepted by civilizednations. As a result ofthe invalidity ofwar, the USA andits allies cannot escape from legal responsibility. Not only because its military aggression was not permitted by the Security Council, butalso because the role ofmilitar troops did hotcomply the demand ofthe 1948 Geneva Convention. Thousand civilians of Iraq aiid'public facilities were ruined toprove in significant that USA should take responsibility both collectively or individually, especially in treating bodly prisoners in Guantanamo andAbu Ghraib.